Experimental investigations of punching shear concrete slabs with different types of transverse reinforcement - Urban, Tadeusz; Krawczyk, Łukasz; Gołdyn, Michał (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The results of support zone thick concrete slabs experimental investigation are presented in the paper. The experimental program consisted of 4 square reinforced concrete flat models to 1:2 scale made of the same concrete with the same dimensions and the same flexural reinforcement. The aim of tests was proved the influence of different transverse reinforcement types on punching shear load capacity. One of the models was a comparative slab made without transverse reinforcement. In the other slabs three types of transverse reinforcement were used: typical stirrups enclosing flexure reinforcement, stirrups situated between flexure reinforcement and ladders. The test results show a few percent difference in load capacity between models with transverse reinforcement, the most effective were typical stirrups enclosing the main reinforcement.